Discovering The Organizational Structure - Marilyn N. Norman; Joy C. Jordan (EDIS)
4-H is made possible through the cooperative efforts of the Cooperative State Research, Education and Extension Service of the United States Department of Agriculture (CSREES/ USDA) in Washington D.C., the University of Florida land-grant University Cooperative Extension System and its partnering institutions, and the county governments throughout Florida. These public dollars are extended by private monies raised by the Florida 4-H Foundation, local foundations, individual 4-H staff and volunteers, and the National 4-H Council. Local sponsors, partners, donors, alumni, and others provide resources and incentives for educational programs, events and recognition. This document is 4-HS FS101.3, one of a series of the Florida 4-H Program, UF/IFAS Extension. Published May 2006.